ISSUES FACING BY NON-NATIVE SPEAKERS IN ACADEMIC WRITING: A LITERATURE REVIEW - Kosimova Khilola Muzaffar kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
This paper is dedicated to identifying widely spread issues among non-native speakers while their writing academic texts. Academic writing is thought to have a tendency not to break a formal writing of indifference and meticulousness, allowing both authors and readers to emanate an air of impartiality. This is achieved when writers seek for privacy and equality in their textual output while employing formalities elements in their pursuit of authenticity, objectivity. Moreover, the challenges and proven solutions are provided in this review.